Feeding habits and multifunctional classification of soil‐associated consumers from protists to vertebrates. (20th January 2022) - Potapov, Anton M.; Beaulieu, Frédéric; Birkhofer, Klaus; Bluhm, Sarah L.; Degtyarev, Maxim I.; Devetter, Miloslav; Goncharov, Anton A.; Gongalsky, Konstantin B.; Klarner, Bernhard; Korobushkin, Daniil I.; Liebke, Dana F.; Maraun, Mark; et al.
ABSTRACT: Soil organisms drive major ecosystem functions by mineralising carbon and releasing nutrients during decomposition processes, which supports plant growth, aboveground biodiversity and, ultimately, human nutrition. Soil ecologists often operate with functional groups to infer the effects of individual taxa on ecosystem functions and services. Simultaneous assessment of the functional roles of multiple taxa is possible using food‐web reconstructions, but our knowledge of the feeding habits of many taxa is insufficient and often based on limited evidence. Over the last two decades, molecular, biochemical and isotopic tools have improved our understanding of the feeding habits of various soil organisms, yet this knowledge is still to be synthesised into a common functional framework. Here, we provide a comprehensive review of the feeding habits of consumers in soil, including protists, micro‐, meso‐ and macrofauna (invertebrates), and soil‐associated vertebrates. We have integrated existing functional group classifications with findings gained with novel methods and compiled an overarching classification across taxa focusing on key universal traits such as food resource preferences, body masses, microhabitat specialisation, protection and hunting mechanisms. Our summary highlights various strands of evidence that many functional groups commonly used in soil ecology and food‐web models are feeding on multiple types of food resources. In many cases, omnivory is observed down to the species level of taxonomic resolution, challenging realism of traditional soil food‐web models based on distinct resource‐based energy channels. Novel methods, such as stable isotope, fatty acid and DNA gut content analyses, have revealed previously hidden facets of trophic relationships of soil consumers, such as food assimilation, multichannel feeding across trophic levels, hidden trophic niche differentiation and the importance of alternative food/prey, as well as energy transfers across ecosystem compartments. Wider adoption of such tools and the development of open interoperable platforms that assemble morphological, ecological and trophic data as traits of soil taxa will enable the refinement and expansion of the multifunctional classification of consumers in soil. The compiled multifunctional classification of soil‐associated consumers will serve as a reference for ecologists working with biodiversity changes and biodiversity–ecosystem functioning relationships, making soil food‐web research more accessible and reproducible.